2015
DOI: 10.4103/0973-6131.146057
|View full text |Cite
|
Sign up to set email alerts
|

Age related differences of selected Hatha yoga practices on anthropometric characteristics, muscular strength and flexibility of healthy individuals

Abstract: Background:Physiological benefits of yoga on volunteers of a particular age group are available. However, reports on efficacy of a specific yoga package on the populace of different age groups from similar occupational background is still very limited. Therefore, the present study was conducted to appraise the effect of a specific Hatha yoga package on anthropometric characteristics, flexibility and muscular strength of healthy individuals of different age groups from similar occupational trade.Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…In the physical fitness level test, HG has revealed an improvement of 13.6% after the 16-week TCSB intervention training compared with that before the intervention. Meanwhile, the result was similar to those reported by Sousa et al [ 24 ] and Halder et al [ 25 ]. The main reason was that the regular use of the Tai Chi handle can improve the regulation of the nervous system.…”
Section: Discussionsupporting
confidence: 91%
“…In the physical fitness level test, HG has revealed an improvement of 13.6% after the 16-week TCSB intervention training compared with that before the intervention. Meanwhile, the result was similar to those reported by Sousa et al [ 24 ] and Halder et al [ 25 ]. The main reason was that the regular use of the Tai Chi handle can improve the regulation of the nervous system.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, as a consequence of aging, muscles and connective tissues decay, resulting in a concomitant decrease of strength and flexibility that may limit individuals functional capacity [40]. A reduction in flexibility has also been progressively noted across decennial age groups ranging from 20 to 49 years of age [18], with an average 10 % decrease every 10 years. Such reduction may significantly affect the activities of daily living and reduce the quality of life in adults [40].…”
Section: Introductionmentioning
confidence: 99%
“…In a review it has been noted that yogic training can reduce body weight from 1.5 per cent to 10.1 per cent in healthy adults and from 1.5 per cent to 13.6 per cent in adults with hypertension/ cardiovascular disease or type 2 diabetes mellitus 14 . In our previous study we have also observed that body weight decreased (5.1 %) after 12 weeks of yoga intervention 15 . It has also been observed in the same study that body mass index (BMI) of the healthy male volunteers of the age group 30-39 years and 40-49 years were higher and classified as 'overweight'.…”
Section: Effect Of Yogic Practices On Different Physiological Systems: 21 Effect Of Yogic Practices On Body Weight and Muscle Strengthmentioning
confidence: 60%